2020
DOI: 10.1177/1558944719895782
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Distal Radius Fracture: Does Early Activity Postinjury Lead to a Lower Incidence of Complex Regional Pain Syndrome?

Abstract: Background: The optimal treatment for a distal radius fracture (DRF) remains an ongoing discussion. This study observed whether early activity postinjury can lead to the prevention of type 1 complex regional pain syndrome (CRPS-1). Method: Patients who underwent nonoperative treatment for a DRF were invited to participate in this study. Patients followed an exercise program with progressive loading exercises at home immediately after cast removal. After a minimum of 3 months, patients were interviewed by telep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…There are suggestions that we should stop stigmatizing CRPS as a severe debilitating disease and rather describe it as a variation of the healing process. 27 , 28 This view is supported by recent insights into the importance of the length of cast immobilization and prevention of disuse in the development of CRPS after a DRF. 14 16 For example, Terkelsen et al showed that 4 weeks of forearm immobilization causes symptoms very similar to those associated with CRPS.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…There are suggestions that we should stop stigmatizing CRPS as a severe debilitating disease and rather describe it as a variation of the healing process. 27 , 28 This view is supported by recent insights into the importance of the length of cast immobilization and prevention of disuse in the development of CRPS after a DRF. 14 16 For example, Terkelsen et al showed that 4 weeks of forearm immobilization causes symptoms very similar to those associated with CRPS.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to the length of immobilization, informing the patient properly, managing the patient’s expectations and encouraging normal use of the limb, with for example an active home exercise programme, is evenly so important to manage the psychological impact of a trauma and thereby prevent disuse and disproportionate pain. 28 An active home exercise programme is often based on the same principles as PEPT treatment, namely the assumption that behavioural and psychological factors can exacerbate pain and dysfunction. 23 , 31 Further research should be done to investigate whether short immobilization periods including home exercise programmes for DRF, is safe and leads to less posttraumatic pain and better patient reported outcomes.…”
Section: Discussionmentioning
confidence: 99%